Effects of interfacial transition layers on the electrical properties of individual Fe30Co61Cu9/Cu multilayer nanowires1. Issue 2 (18th November 2015) - Ma, Hongbin; Zhang, Junwei; Zhang, Hong; Lan, Qianqian; Guan, Chaoshuai; Zhang, Qiang; Bai, Feiming; Peng, Yong; Zhang, Xixiang
Abstract : We accurately measure the electrical properties of individual Fe30 Co61 Cu9 /Cu multilayered nanowires using nanomanipulators in in situ SEM to reveal that interfacial transition layers are influential in determining their transport behaviors. Abstract : In this work, we accurately measure the electrical properties of individual Fe30 Co61 Cu9 /Cu multilayered nanowires using nanomanipulators in in situ scanning electron microscopy to reveal that interfacial transition layers are influential in determining their transport behaviors. We investigate the morphology, crystal structure and chemistry of the Fe30 Co61 Cu9 /Cu multilayered nanowires to characterize them at the nanoscale. We also compare the transport properties of these multilayered nanowires to those of individual pure Cu nanowires and to those of alloy Fe30 Co61 Cu9 nanowires. The multilayered nanowires with a 50 nm diameter had a remarkable resistivity of approximately 5.41 × 10 −7 Ω m and a failure current density of 1.54 × 10 11 A m −2 . Detailed analysis of the electrical data reveals that interfacial transition layers influence the electrical properties of multilayered nanowires and are likely to have a strong impact on the life of nanodevices. This work contributes to a basic understanding of the electrical parameters of individual magnetic multilayered nanowires for their application as functional building blocks and interconnecting leads in nanodevices and nanoelectronics, and also provides a clear physical picture of a single multilayered nanowire which explains its electrical resistance and its source of giant magnetoresistance.